"Who will resolve this conflict if the politicians don't?": Members' of Parliament understandings of the Kurdish conflict in Turkey. Issue 2 (10th April 2017) - Uluğ, Özden Melis; Cohrs, J. Christopher
Abstract : Purpose: Exploring the understandings of conflict held by Members of Parliament (MPs) provides a meaningful picture of a conflict in a particular society. The aim of the study is to explore the Kurdish conflict understandings among MPs in Turkey. Design/methodology/approach: The current research used Q methodology, which is a suitable method to identify socially shared perspectives and to identify intra- and inter-group differences, and Entman's (1993) frame analysis to explore subjective understandings of the Kurdish conflict. Data were collected from 23 MPs from four political parties. Findings: The analysis revealed four qualitatively distinct viewpoints: Turkish Nationalist view, Social Democratic view, Conservative-Religious view and Pro-Kurdish view. Originality/value: This study contributes to the understanding of political parties' perspectives on the Kurdish conflict in Turkey by representing each political party's priorities and concerns. The meaning of these priorities and concerns, implications for conflict resolution and the usefulness of the Q methodology for exploring conflict understandings are also discussed.